The command of biotechnology and merciful conquest in military opposition. - Guo J; Guo, Ji-Wei (Military Medicine, 2006)
Biotechnology has an increasingly extensive use for military purposes. With the upcoming age of biotechnology, military operations are depending more on biotechnical methods. Judging from the evolving law of the theory of command, the command of biotechnology is feasible and inevitable. The report discusses some basic characteristics of modern theories of command, as well as the mature possibility of the command theory of military biotechnology. The evolution of the command theory is closely associated with the development of military medicine. This theory is expected to achieve successes in wars in an ultramicro, nonlethal, reversible, and merciful way and will play an important role in biotechnological identification and orientation, defense and attack, and the maintenance of fighting powers and biological monitoring. The command of military biotechnology has not become a part of the virtual military power yet, but it is an exigent strategic task to construct and perfect this theory.